ADAKAH COLLABORATIVE GOVERNANCE DALAM KEBIJAKAN SOSIAL PASCA BENCANA DI PROVINSI BANTEN? - Thahir, Baharuddin (Jurnal Bina Praja, 2022)
Social policies include increased social protection, approaches to improving living standards, and access to decent work. The description discusses two concepts, namely collaborative governance and the concept of social policy. Methodologically and technically, the two concepts are side by side in the context of implementing decentralization policies. Collaborative governance as collaboration is a relationship designed to solve a problem through the creation of solutions in conditions that are full of limitations  (Ansell & Gash, 2008). At the same time, the social policy responds to social problems, which tends to ignore the assessment of some people that they are not in a socially problematic condition (Spicker, 2014). social policy has many forms, such as health, education, housing, and other social services. The method uses a descriptive qualitative and qualitative verification analysis strategy model. Post-disaster handling, collaborative governance is applied through the government's efforts to carry out recovery that focuses on the residential, economic, infrastructure, social and cross-sectoral sectors. The results also show obstacles in collaborative governance, such as delays in building houses for the community, mismatch of specifications between what was promised and what was received by the community, and low public understanding. This study also shows that post-disaster management collaborative governance can be implemented using several strategies divided by sector and sub-sector; the right communication pattern increases community involvement in the entire post-disaster management process in Banten province. All strategies would be better if packaged in the form of government innovation. This means that post-disaster management, especially in repair and development efforts, is an important agenda for government collaboration.